Lipid and protein changes related to quality loss in frozen sardine (Sardina pilchardus) previously processed under high-pressure conditions - Méndez, L. (2022)
This research focuses on biochemical changes related to quality loss in frozen (−18 °C for 9 months) sardine (Sardina pilchardus) previously subjected to high-pressure (HP) processing (125–200 MPa). The inhibition (p < 0.05) of lipid hydrolysis development (lower free fatty acid formation and lipase activity), observed in frozen sardine as a result of the previous HP treatment, increased with the pressure level applied. Several parameters including peroxide value, thiobarbituric acid index, fluorescent compounds, and polyenes showed that the applied HP conditions prior to sardine freezing did not increase lipid oxidation. Also, HP did not induce a substantial modification of acid phosphatase and cathepsins B and D activities, and the electrophoretic patterns of sarcoplasmic and myofibrillar protein fractions did not change. However, HP processing led to a decrease in myofibrillar protein content in frozen pressure-treated fish, an effect that was higher in 175- and 200-MPa treated samples. In conclusion, this research showed that pressure treatments in the 125–200- MPa range with holding time of 0 min cause only minor modifications in biochemical indicators of deterioration throughout the subsequent frozen storage of samples for up to 9 months. This study shows the need to optimize HP conditions, particularly in the case of applications combining HP treatments, frozen storage, and thawing to obtain products with high quality and commercial viability.